Analysis of Background Ionospheric Effects on Geosynchronous SAR Imaging - Ji, Yifei; Zhang, Qilei; Zhang, Yongsheng; Dong, Zhen (Společnost pro radioelektronické inženýrství, 2017)
Background ionospheric propagation effects are adverse to the performance of Geosynchronous Synthetic Aperture Radar (GEO SAR) system. This paper focuses on the background ionospheric phase advance, which can be modelled as a function of Slant Total Electron Content (STEC). The dispersive feature of the phase advance caused by the background ionosphere could be able to distort the GEO SAR range-imaging. Furthermore, for GEO SAR, the integration time is ultra-long and the coverage is ultra-large, thus temporal and spatial distributions of the background ionosphere have to be taken into account. The resultant ionospheric phase variations might decorrelate the azimuth signal and then lead to azimuth-imaging deteriorations. In this paper, the theoretical model of the background ionospheric effects on GEO SAR imaging is established and in-depth analyses are presented. Finally, theoretical analyses are validated by the signal-level simulation.
Keywords: Geosynchronous Synthetic Aperture Radar (GEO SAR); imaging; background ionosphere; Total Electron Content (TEC); Slant Total Electron Content (STEC)